Giant Retrorectal Epidermoid Cyst Masquerading as a Perianal Swelling - Reem Al-Shoura; Haifaa Malaekah; Waddah Al Bassam (Case Reports in Surgery)
A retrorectal epidermoid cyst is an uncommon congenital lesion that arises from the remnants of the embryonic tissues. This type of cyst is difficult to diagnose before surgery. In this study, we report a rare case of a giant retrorectal epidermoid cyst in a 30-year-old woman. Initially, the condition was diagnosed as a perianal abscess and treated with incision and drainage. Since the abscess recurred, a pelvic magnetic resonance imaging was ordered, which revealed an 8.2 cm perianal cyst with appearance not compatible with an abscess. Postsurgical histologic analysis confirmed a retrorectal epidermoid cyst. Postoperative course was uneventful, and the woman was discharged on postoperative day 3. She was doing well at 4 months of follow-up. This report suggests that retrorectal cysts should be considered in cases of recurrent perianal swellings/abscesses.